STUDI PENGARUH SCREEN MESH TERHADAP INTENSITAS TURBULENSI PADA TEROWONGAN ANGIN SIRKUIT TERBUKA - Nurul Mahilda; Cecep E Rustana; Umiatin Umiatin (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Screen Mesh is a filter made of wire that serves to remove the fine vortex structure by equating the speed variation of wind flow in the wind tunnel. Adding the screen mesh is to determine the effect of screen mesh to the value of turbulence intensity on open circuit wind tunnel. In this study, it has been made three pieces of screen mesh with each diameter of 46.5 cm, 48.5 cm and 50.5 cm. The tests was carried out by using screen mesh with rhombic mesh with 3 mm diagonal length that placed on X/L 0.67, 0.8, and 0.93. This research was conducted by comparing the results of turbulence intensity measurements between the wind tunnel without screen mesh, wind tunnel with honeycomb and screen mesh, as well as wind tunnel with only screen mesh so that we can know the flow quality in the wind tunnel. The test results indicated that the screen mesh has the ability to minimize the turbulence intensity. The wind tunnel that is installed using a honeycomb cell has 6 mm diameter and the 3 pieces of screen mesh has the lowest turbulence intensity that is I â‰ˆ 0,0242.Keywords: wind tunnel, screen mesh, turbulence intensity.